PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS ANDROID MENGGUNAKAN MIT APP INVENTOR PADA MATERI FUNGSI KOMPOSISI DAN FUNGSI INVERS KELAS X IIS SMA PGRI 3 PADANG - Nalsri, Sherly Yulia; Rahmi, Rahmi; Jufri, Lucky Heriyanti (Program Studi Pendidikan Matematika FKIP Universitas Islam Darul Ulum, 2023)
The development of technology in the world of education uses media in mathematics learning, teachers strive to make learning media and teaching materials for the smooth effective learning process. In the learning process, an IT-based learning media is needed that can attract the attention of students during the learning process, especially in the material Composition Function and Inverse Function. This study aims to develop android-based learning media using MIT App Inventor on valid and practical material for Composition Function and Inverse Function class X IIS SMA PGRI 3 Padang. This research uses R&D (Research and Development) research using Plomp development which consists of three stages, namely preliminary phase, prototyping phase and assessment phase. This research was only carried out until the prototyping phase stage. The results of the validity test showed that android-based learning media using MIT App Inventor on the material Composition Function and Inverse Function obtained a percentage of 91.64% with very valid criteria, the results of the practicality test with class X IIS SMA PGRI 3 Padang obtained a percentage of 85.64% with very practical criteria.